Research progress of LncRNA NEAT1 in psoriasis and its comorbidities - Zhiming TANG; Mengqing JING; Xiao SHAN; Lu LU; Jie LI (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2023)
LncRNA NEAT1 can regulate gene expression by the formation of paranuclear plaques, acting as ceRNA, and epigenetic modification, and subsequently participating in the physiological and pathological processes such as inflammatory response, immune response, cell proliferation and differentiation. LncRNA NEAT1 is linked to the pathogenesis of many diseases. LncRNA NEAT1 plays an important pathogenic role in psoriasis and its comorbidities, which exhibit high expression levels of LncRNA NEAT1. Here we review the profile of LncRNA NEAT1 and its research progress in psoriasis and its comorbidities.